RESPON APLIKASI PUPUK NPK DAN JENIS AMELIORAN TERHADAP SIFAT FISIKA TANAH DAN PERTUMBUHAN TANAMAN PADI PADA LAHAN SAWAH BUKAAN BARU - Elvrida Rosa; Sri Fitri (Jurnal Agrotek Lestari, 2018)
The study was conducted in Abeuk Reuling village of Sawang subdistrict, North Aceh District. The aims of this study was to determined the response of NPK fertilizer, the type of ameliorants and the interaction between both treatment of the soil physic properties and the growth of paddy rice on new paddy field. The methods of this study based on a randomized block design factorial 4 x 4 and repeated 3 times, which consists of a dose of NPK and the type of ameliorants. The results showed that the interaction of dose of NPK fertilizer and type of ameliorants is highly siginificant effect on the soil physic properties that is bulk density, soil porosity dan aggregate stability index. While the single effect of dose of NPK fertilizer and type of ameliorants is highly siginificant effect on plant growth that is plant height at 30, 45, 90 days after planting and the number of tillers per hill. Keywords: ameliorant, new paddy field, NPK fertilizer, soil physic properties